The business of travel: Agency operations and administration : Instructor's guide to accompany / Dennis L.Foster - Dennis, L.Foster
The Instructor's guide is designed as a teaching guide in conjunction with the student text, The Business of Travel: Agency Operation and Administration. The textbook and the curriculum of which it is a part evolved from a corporate training program of a major retail travel organization. This textbook emphasizes practical problems to which a working knowledge of agency operations and administration is applied in the workplace. Students "learn by doing", with ample exposure to hands-on exercises, case studies, and role playing.